Functionalized Biomimetic Magnetic Nanoparticles as Effective Nanocarriers for Targeted Chemotherapy. (13th May 2019) - Peigneux, Ana; Oltolina, Francesca; Colangelo, Donato; Iglesias, Guillermo R.; Delgado, Angel V.; Prat, Maria; Jimenez‐Lopez, Concepcion
Abstract: Novel MamC‐mediated biomimetic magnetic nanoparticles (BMNPs) are proposed as valuable carriers for targeted chemotherapy because of the size (36 ± 12 nm) and of surface properties conferred by MamC coating. They are super‐paramagnetic at room and body temperatures, have a large magnetic moment per particle, mediate hyperthermia, are cytocompatible, and, having a negative surface charge at physiological pH, can be efficiently coupled with DOXOrubicin (DOXO) and a monoclonal antibody (mAb) directed against the human Met/hepatocyte growth factor receptor (overexpressed in many cancers) displaying coupling stability, while releasing DOXO at acidic pH. This release can be enhanced by hyperthermia. The DOXO‐mAb‐BMNPs selectively recognize Met, bind efficiently to Met + tumor cells, and discharge DOXO within their nuclei more efficiently than DOXO‐BMNPs, exerting cytotoxicity. These data represent proof of concept for future in vivo experiments in which the controlled dual targeting (mAb‐mediated and magnetic) approach and combined (chemotherapy and hyperthermia) therapy will be studied. Abstract : MamC‐biomimetic magnetic nanoparticles stably coupled by isothermic adsorption with DOXOrubicin (DOXO) and a monoclonal antibody (mAb) directed against the tumor marker Met/HGFR at physiological pH can release Doxorubicin at acidic pH, exerting targeted cytotoxicity. DOXO release is enhanced by hyperthermia. These data represent proof of concept for future experiments of dual (mAb, magnetic) targeting and combined (chemotherapy and hyperthermia) therapy.